Gasotransmitters are emerging as new guard cell signalling molecules and regulators of leaf gas exchange - García Mata, Carlos (2013)
Specialized guard cells modulate plant gas exchange through the regulation of stomatal aperture. The size of the stomatal pore is a direct function of the volume of the guard cells. The transport of solutes across channels in plasma membrane is a crucial process in the maintenance of guard cell water status. The fine tuned regulation of that transport requires an integrated convergence of multiple endogenous and exogenous signals perceived at both the cellular and the whole plant level. Gasotransmitters are novel signaling molecules with key functions in guard cell physiology. Three gasotransmitters, nitric oxide (NO), carbon monoxide (CO), and hydrogen sulfide (H2S) are involved in guard cell regulatory processes. These molecules are endogenously produced by plant cells and are part of the guard cells responses to drought stress conditions through ABA-dependent pathways. In this review, we summarize the current knowledge of gasotransmitters as versatile molecules interacting with different components of guard cell signaling network and propose them as players in new paradigms to study ABA-independent guard cell responses to water deficit.